Alpha-linolenic acid content and expression of KASII and FAD3 in perilla seed associated with altitude of cultivation areas - Orada Chumphukam (2020)
© 2019 Science Society of Thailand under Royal Patronage. All rights reserved. Perilla frutescens is commonly used as an n-3-fatty acid source for people living in Northern Thailand. However, cultivated areas are limited because it apparently requires specific growth conditions. Our results suggested that perilla seeds grown at higher altitude in Maehongson province contained more α-linoleic acid (ALA) contents than seeds collected from Chiang Rai and Nan provinces. Furthermore, mass spectrometry, proteomic and gene expression analysis revealed that the increase of KASII and FAD3 proteins was associated with mRNA expression and ALA production. Predictive bioinformatics analysis demonstrated two important transcription factor binding sites, AP2 and B3, are responsible for kasII and fad3 genes, respectively. The AP2 and B3 transcription factor families were known to be responsible for abiotic stress such as drought and temperature changes. From our observation, geographical factors could possibly influence the expression of genes related to fatty acid production. Furthermore, plant responses to abiotic stress environments contribute to the increase of kasII and fad3 genes and their protein expression. However, responsive transcription factors will be further studied as well as other geographical influences for a proof of concept and also to improve growing methods in order to increase perilla productivity.